Features of the protective actions related to health processed in Medellin, Colombia - Rodríguez Tejada, Claudia Milena; Molina Marín, Gloria; Jiménez, Santiago Alejandro (Investigación y Educación en Enfermería, 2010)
<!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 9]> Normal 0 21 false false false ES-CO X-NONE X-NONE <![endif]--><!-- [if gte mso 9]> <![endif]--><!-- /* Font Definitions */ @font-face {font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-520092929 1073786111 9 0 415 0;} @font-face {font-family:NewsGothicBT-Bold; panose-1:0 0 0 0 0 0 0 0 0 0; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-format:other; mso-font-pitch:auto; mso-font-signature:3 0 0 0 1 0;} @font-face {font-family:NewsGothicBT-Roman; panose-1:0 0 0 0 0 0 0 0 0 0; mso-font-charset:0; mso-generic-font-family:auto; mso-font-format:other; mso-font-pitch:auto; mso-font-signature:3 0 0 0 1 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin-top:0cm; margin-right:0cm; margin-bottom:10.0pt; margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-fareast-language:EN-US;} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-fareast-language:EN-US;} .MsoPapDefault {mso-style-type:export-only; margin-bottom:10.0pt; line-height:115%;} @page WordSection1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.WordSection1 {page:WordSection1;} --><!-- [if gte mso 10]> <![endif]--> Objective: to describe the health right infringement features, as reflected in the protective actions processed in the city of Medellin (Colombia). Methodology: retrospective descriptive study, in which the protective actions processed in the Antioquia’s sectional direction court during the years 2001-2007 were analyzed. A randomized sampling was taken, stratified by defendant entity and years of protective actions rulings. Results: 79% of the people who filed protective actions were affiliated to the contributive tax regime, 88% of them required health services, medicines, or medical supplies included in the Mandatory Health Plan. From the affiliates to the subsidy regimen 57% required attention and services included in the benefit plan. 62% of the people asked for integral attention. The circulatory and osteomuscular system diseases took a bigger number of people to file a protective action (19% and 15%) respectively. Conclusion: Most of the people regardless the type of affiliation to the General Social Security System, ask for health attention and services included in their benefit plan through the protective action.